Hematological Malignancy-Derived Small Extracellular Vesicles and Tumor Microenvironment: The Art of Turning Foes into Friends - Ernesto Gargiulo; Jerome Paggetti; Etienne Moussay (Cells, 2019)
Small extracellular vesicles (small EVs) are commonly released by all cells, and are found in all body fluids. They are implicated in cell to cell short- and long-distance communication through the transfer of genetic material and proteins, as well as interactions between target cell membrane receptors and ligands anchored on small EV membrane. Beyond their canonical functions in healthy tissues, small EVs are strategically used by tumors to communicate with the cellular microenvironment and to establish a proper niche which would ultimately allow cancer cell proliferation, escape from the immune surveillance, and metastasis formation. In this review, we highlight the effects of hematological malignancy-derived small EVs on immune and stromal cells in the tumor microenvironment.